Perspectives of fishers on the incident of fish kills in Rivers State Coastal Waters, Nigeria - Olopade, Olaniyi Alaba; Dienye, Henry Eyina; Oroma, Bestman Success (Universitas Malikussaleh, 2024)
This study was conducted to assess fishermen's perspectives on the massive fish kill incident in coastal waters in Rivers State, Nigeria. Primary data were collected using questionnaires from 101 randomly selected fishermen and the data were evaluated using descriptive statistics. The results showed that fishing was the main occupation of the respondents and the interviewed fishermen have fishing experience in the region studied and knowledge of their fishery. The results showed that 53.3 percent of fishermen attributed the strange phenomenon to pollution, while 19.8 percent cited infection and disease as the cause of the fish kills. The majority of respondents (94%) reported that croaker fish species were particularly affected in the study area. Other observations include fish swimming on the surface or jumping onto shore and affected fish washing up on shore. The unusual appearances of the dead fish commonly reported by respondents were as follows: fin rot, open mouth, disease spots and deep blue gills. About half of the respondents (50.5%) gave a range of 1,000 - 5000 dead fish and a size class of the dead fish of more than 30 cm. Most respondents (79.2%) indicated that the government has not taken any action. Few of those surveyed reported government action on sea clean-up exercises to remove dead fish and end oil spillage and bunkering as measures put in place by the government. The study recommended partnerships between the government and fishermen and fishermen's groups as stakeholders are required to address the concerns about marine waters.Keyword: Coastal waters; Fishers; Mass fish mortality; Nigeria